2013
DOI: 10.1088/1475-7516/2013/10/024
|View full text |Cite
|
Sign up to set email alerts
|

Two field matter bounce cosmology

Abstract: We re-examine the non-singular Matter Bounce scenario first developed in [20], which starts with a matter-dominated period of contraction and transitions into an Ekpyrotic phase of contraction. We consider both matter fields, the first of which plays the role of regular matter, and the second of which is responsible for the non-singular bounce. Since the dominant matter field is massive, the induced curvature fluctuations are initially not scale-invariant, whereas the fluctuations of the second scalar field (w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
170
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(173 citation statements)
references
References 71 publications
2
170
1
Order By: Relevance
“…This can also be seen from the expression (22), owing to the fact that a Big Rip requiresḢ > 0, and we discussed this issue previously, below Eq. (14). But we can explicitly show that indeed a phantom dark energy era occurs at very late times, since a direct calculation yields that, as t → t s , and during the dark energy era, the EoS becomes approximately equal to,…”
Section: Figmentioning
confidence: 77%
“…This can also be seen from the expression (22), owing to the fact that a Big Rip requiresḢ > 0, and we discussed this issue previously, below Eq. (14). But we can explicitly show that indeed a phantom dark energy era occurs at very late times, since a direct calculation yields that, as t → t s , and during the dark energy era, the EoS becomes approximately equal to,…”
Section: Figmentioning
confidence: 77%
“…So we write the modified Friedmann equations (57) and (58) in the case of unimodular f (T ) gravity as…”
Section: Physics Of Torsion Fluidmentioning
confidence: 99%
“…In these models, one ought to be aware of the potential graceful exit problem as well as the gradient instability issue. For example, in a concrete cosmology of two-field matter bounce [92], it was found that the model can be free from these dangerous issues with cosmological perturbations evolving through the nonsingular bouncing phase almost unchanged [93]. Accordingly, the tensor-to-scalar ratio could be too large to explain the CMB observations and may require a curvaton mechanism [23] to give rise to an enhancement on curvature perturbations from entropy fluctuations.…”
Section: Problems With Particular Bounce Modelsmentioning
confidence: 99%